Implementasi Algoritma Fuzzy Tipe-2 Untuk Penentuan Kriteria Kota Berdasarkan Standar Smart City - Alfachruddin, M. Nabil Fahd; Kurniawan, Fachrul; Arif, Yunifa Miftachul (Department of Informatics Engineering, 2019)
City is a role model which represents the advancement of technology and the existence of prosperity. An improvement of technology should be used as a key to manage city’s prosperity. Many standards used to measure the value of city’s prosperity. One of that standards is smart city standard. It used factors which define city’s prosperity, hence it needs a key factor that allows the standard to produce a crisp result from the available factors. There are 6 key variables of city’s prosperity of smart city standard, they are smat governance, smart mobility, smart people, smart economy, smart environment dan smart mobility. Type-2 fuzzy algorithm is used to determine city prosperity’ grade using smart city standard. The algorithm is implemented in a game of Malang city’s miniature which named after Malang Urban. In this research several in-game experiments are made to get values that meet a specified rules. The values consist 73,33% of not ready category, 6, 67% of standard category, and 20% of good smart category of all in-game attempts.